Homecoming / vol. 2 - Cabot, Meg (Tokyopop, 2008)
Ellie pushes forward with her plans for a big dinner party to reunite her boyfriend Will with his parents, in spite of her misgivings over his brother Marco, who is newly released from the mental hospital, and Mr. Norton's insistence that Will is the reincarnation of King Arthur.